The Role of Nurses in Preventing Complications from the Use of Extracorporeal Membrane Oxygenation in Critically Ill Pediatric Patients - Kampan, Pilailak (Princess of Naradhiwas University Journal, 2025)
Extracorporeal Membrane Oxygenation (ECMO) is a device used to temporarily support heart and lung function in critically ill pediatric patients. It acts as an artificial lung to exchange gases and as an artificial heart to pump blood and control blood circulation in pediatric patients with acute lung and heart failure. Common complications during ECMO use include blood loss, cerebral hemorrhage, impaired kidney function, infection, and complications from device failure, such as membrane oxygenator failure and pump failure. This academic article focuses on the role of nurses in preventing complications during ECMO use in critically ill pediatric patients based on literature reviews and the authors' experience. Key practice guidelines can be summarized as closely monitoring electrocardiograms and vital signs, assessing level of consciousness and pupillary light response, measuring brain tissue oxygen levels by Near Infrared Spectroscopy (NIRS), observing and recording the characteristics, volume, and location of blood loss, administering anticoagulants (heparin), monitoring fluid intake and output, caring strictly with aseptic technique, preventing kinking, bending, pulling, or dislodgement of vascular catheters, checking for clots and air bubbles in the system, and regularly assessing the color of venous and arterial catheters. These guidelines reflect the important role of nurses in monitoring and preventing complications during ECMO use, which requires comprehensive knowledge, skills, and care to promote safety and the best possible outcomes for critically ill pediatric patients.